(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article discusses the issues of soil-climatic zones of the Issyk-Kul biosphere. Features of their geographical position on the surface of a given territory. Different influence of natural factors on the formation of soil-climatic zones. In recent decades, the state of landscapes has been subjected to increasing anthropogenic pressure from year to year. This is due to many reasons. An important direction in the ecology of soil and climatic zones and the rational use of land is of great importance for the national economy, respect for nature is the main task for every person. The article notes that the soil-climatic zones of the Issyk-Kul biosphere are very diverse and original. However, among the soil-climatic zones there are quite significant areas that have suffered from anthropogenic factors.